Realising the potential of user surveys for improving academic libraries: The case of St John's College, Cambridge. (September 2019) - Chow, Janet
How can user surveys lead to better decision making to improve libraries? While there are more surveys published on specialised aspects of academic libraries, there are relatively few user surveys published of academic libraries in general. First and foremost this paper argues the user survey is a useful tool for library managers interested in developing their libraries in response to changing user needs, and secondly, for more published accounts of surveys and their usefulness. However, the user survey as a tool for generating evidence-based decision making in libraries fails to achieve its potential if two further important practices are not implemented. First and most importantly, the findings obtained from the survey must be used to inform decision making on managing and leading improvements to the library. This aspect of follow-through from survey findings to management decision making, may well lead to changing resource allocation and priorities, new practices, and improvements to collections and the physical environment. Second, the findings of the survey should be fed back to users as a means of raising their interest and engagement in the academic library as a hub of learning.